Consolidating a Culture of Assessment for Learning: EFL Teachers’ Appropriation of an Assessment Policy through a Virtual Community of Practice - Picón-Jácome, Edgar; Montoya López, Juan Carlos (Colombian Applied Linguistics Journal, 2024)
This participatory action research study inquired about EFL teachers’ appropriation of a language education policy through a virtual community of practice on language assessment literacies. From a critical sociocultural perspective, the participants’ appropriation was studied aiming at understanding how their discourses and praxes embraced an AfL culture. During the process, teachers inquired and reflected on their lived experiences as they judged the system’s rationality, sustainability, and justice. The analysis yielded evidence of the consolidation of the policy through five main findings: (1) The community unlocked space for the participants to develop understandings and propose actions. (2) They openly debated their interpretations of the system tenets and shared their practical knowledge. (3) In doing so, they tested their knowledge, beliefs, and self-declared purposes against the official assessment policy. (4) The interactions permitted to infer their internalization of assessment as a socially constructed practice. (5) The learning gained throughout the process allowed for the adjustment of the evaluation system to maximize its practicality and positive impact.